Editorial - Teye, Prof. G. A. (UDS International Journal of Development, 2023)
The UDS International Journal of Development (UDSIJD) has published the second Issue for 2022 (Vol. 9 No. 2). There are nine papers in this Issue – five in the humanities and four in the Sciences.The aim of the UDSIJD is to ensure that it remains an excellent platform for researchers to publish their scholarly output on a regular and sustained basis. The Journal also hopes that there would be a more varied representation from diverse fields in our subsequent Issues especially that we are a multi and inter-disciplinary Journal.Researchers, academics, development practitioners and entrepreneurs are therefore encouraged to take advantage of this open access platform to find relevant local content which would enhance their research and decision-making processes.The Editorial Team would always be grateful to the University Management, authors, reviewers and staff of the Journal and all who in various ways have influenced the successful publication of this Issue. The Editor-in-Chief Prof. G. A. Teye